John Barry papers - Barry, John, 1745-1803.
Correspondence, ships' records and documents, and personal and biographical material, chiefly relating to naval matters and trade.
In part, negative photocopies made in 1940.
Continental and U.S. naval officer and shipowner.
Collection material in English.
Keywords: Ship's papers -- 18th century; Ship's papers -- 19th century; United States. -- Continental Navy; United States. -- Navy -- History -- 18th century; United States -- Commerce -- History -- 18th century; Naval officers; Shipowners